Work Readiness based from Work Motivation, Attitude in Entrepreneurship and Women's Clothing Skill Competency on Vocational High School Students - Ida Ayu Reviena Damasanti (Jurnal Pendidikan Sains, 2014)
Kesiapan Kerja Ditinjau dari Motivasi Kerja, Sikap Kewirausahaan, dan Kompetensi Keahlian Busana Wanita pada Siswa SMKN Abstract: The study has a purpose to measure the occupational readiness of Public Vocational High School students in Bali Province. The result reveals the following findings. (1) The descriptive analysis shows that the occupational readiness has mean good category. The occupational motivation has mean good category. The entrepreneurship attitude has mean fair category. The expertise competence of female dress has mean good category. (2) Work motivation, entrepreneurial attitude, competence of women’s fashion expertise can explain job readiness. (3) The partial correlational analysis shows the significant correlation between independent variables and dependent variables. The recapitulation from three independent variables shows that the highest partial correlational coefficient is found in the correlation between occupational motivation and occupational readiness, and then followed by the correlation between the expertise competence of female dress and occupational readiness and correlation between entrepreneurship attitude and occupational readiness of students Key Words: work readiness, motivation, attitudes, competencies, vocational school Abstrak: Penelitian ini bertujuan untuk mengukur kesiapan kerja pada siswa SMKN di Provinsi Bali. Hasil penelitian mengungkapkan bahwa: (1) analisis deskriptif menunjukkan kesiapan kerja dengan kategori baik, motivasi kerja dengan kategori baik, sikap kewirausahaan dengan kategori cukup baik, kompetensi keahlian busana wanita dengan kategori baik, (2) motivasi kerja, sikap kewirausahaan, dan kompetensi keahlian busana wanita mampu menjelaskan kesiapan kerja, (3) analisis korelasi parsial menunjukkan hubungan yang signifikan antara variabel bebas dengan variabel terikat. Rekapitulasi ketiga variabel bebas menunjukkan koefisien korelasi parsial terbesar ada pada hubungan motivasi kerja dengan kesipan kerja, kemudian kompetensi keahlian busana wanita dengan kesiapan kerja, dan sikap kewirausahaan dengan kesiapan kerja siswa.Kata kunci: kesiapan kerja, motivasi, sikap, kompetensi, SMKN